Manufactured sand for the development of reinforced concrete spun pipes. (2022) - Mahaa Lakshmi, N.K.; Chella Gifta, C.; Sankar Kumar, S.; Stephan, S.
Highlights: The effect of Msand replacement as a fine aggregate for the manufacture of RCC spun pipes was investigated. Addition of Manufactured sand replacement slightly decreases the concrete workability. Msand as a fine aggregate replacement increases then the compressive strength decreases and 50% replacement produces highest compressive strength. RCC spun pipes manufactured with 50% replacement shows positive results in Three edge bearing and Hydrostatic test. Abstract: Due to overexploitation of natural resources, the deficiency of river sand as a fine aggregate is a major problem and manufactured sand is replaced as a suitable alternative material. This paper investigates the influence of Manufactured sand as a replacement for fine aggregate material in the manufacture of RCC spun pipes. M35 grade concrete is prepared with cement, coarse aggregate, superplasticizers, and river sand is replaced with 50%, 75% and 100 % manufactured sand. Test results shows that the compressive strength of concrete cubes with 50% replacement levels leads to higher compressive strength at early ages, and their reactivity decreases at later age strength. Test conducted on concrete pipes reveals that the load-carrying capacity of pipes with 50% replacement levels increases and delays the crack formation on the surface and postponed the ultimate failure. Similarly, the hydrostatic test also shows positive results with the addition of MSand. The cost of Manufactured sand is lower than the river sand and it is free from impurities such as silt and clayey matters and it gives a possible solution to the shortage of fine aggregate in the production of RCC pipes.